Human Resource Management Strategy to Improve Company Competitiveness at PT. Agro Niaga Eternal City of Bandung - Muh. Alvianto Putra Arizandi Sadarrudin; Tommy Pusriadi; Lasnoto Lasnoto (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the effect of Human Resource Management (HRM) Strategy on Company Competitiveness, by considering the role of Employee Performance and Employee Innovation as mediating and moderating variables. The research was conducted at PT Agro Niaga Abadi Bandung City by involving 100 respondents as research samples. The method used is quantitative with multiple linear regression approaches, including testing moderation interaction variables. The results showed that HRM Strategy has a significant effect on Company Competitiveness, with a significant value of 0.000 and a coefficient of determination (R²) of 0.972. Employee Performance and Employee Innovation are also proven to have a positive and significant influence on competitiveness, with a significance level of 0.045 and 0.037, respectively. In addition, the interaction between Employee Innovation and Employee Performance shows a significant effect on the company's competitiveness (significance 0.029), which proves that Employee Innovation can positively moderate the relationship between Performance and Competitiveness. These findings confirm that effective HR management strategies, optimal employee performance, and a strong culture of innovation are key factors in building a company's competitive advantage.